Advising by Design: Co-creating Advising Services With Students for Their Success - Mann, Catherine (Frontiers in Education, 2020)
With global trends turning towards increased personalization and expectations of higher education, the question of how to design relevant and high-quality advising services at scale that support learning outcomes, improve the student experience and enhance the acquisition of employability skills is a central challenge for many universities. The emergence of co-creation principles to better shape relevant solutions to engage students can also be applied to advising practice. This article explores the role of design thinking applied to advising at both the strategic and operational levels within one Australian university. With a holistic methodology, design thinking considers the needs of everyone in the system, delivering qualitative data that provides insights into behaviors and drivers that have implications for the ways in which advising services are defined, designed and delivered. It suggests that advising practice and the process of Human Centered Design share methods that can be powerful in bridging the gap that many students perceive between the institutional offering and the student experience.